1,3,4- Thiadiazole and Its Derivatives- A Review on Syntheic Account and Recent Progress on its Phermoacological Activities - Mahadev, Jadhav Kiran; Nandkumar, Chitnis Akshata; Vishveswar, Khandare Aishwarya; P.L, Salve; V.J , Pise (Asian Journal of Pharmaceutical Research and Development, 2024)
Many compounds containing a five-membered heterocyclic ring display exceptional chemical properties and versatile biological activities. The 1,3,4-thiadiazole nucleus is one of the most important and well-known heterocyclic nuclei, which is a common and integral feature of a variety of natural products and medicinal agents. Thiadiazole nucleus is present as a core structural component in an array of drug categories such as antimicrobial, anti-inflammatory, analgesic, antifungal, antiepileptic, antiviral, antineoplastic, and antitubercular agents. The broad and potent activity of thiadiazole and their derivatives has established them as pharmacologically significant scaffolds. The current review focused on the various biological performances exhibited by 1,3,4-thiadiazoles.